1999
DOI: 10.1063/1.123141
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of AlGaN during high-temperature annealing monitored by ultraviolet Raman scattering

Abstract: We have illustrated the use of ultraviolet (UV) Raman scattering to investigate the thermal stability of AlGaN layers with high-aluminum content. The degradation pathway of Al0.72Ga0.28N was monitored for high-temperature treatments up to 1200 °C. For annealing temperatures higher than 1150 °C, the Al0.72Ga0.28N film decomposes: a low- and a high-aluminum composition AlxGa1−xN phase emerge. At 1100 °C, prior to the Al0.72Ga0.28N decomposition, UV Raman scattering detects the buildup of a large strain in the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Ultraviolet excitation wavelengths of 325 nm also allow the study of Al x Ga 1 x N surface properties for aluminium compositions up to x D 0.23. 20,21 Deep-UV micro-Raman spectroscopy is necessary to probe the surface layer of Al x Ga 1 x N films of higher aluminium compositions due to their larger bandgap (using, for example, a frequency-doubled Ar laser (244 nm) as excitation source 22 up to an aluminium composition of x D 0.71). Note that the Al x Ga 1 x N bandgap increases with increasing aluminium composition x.…”
Section: Methodsmentioning
confidence: 99%
“…Ultraviolet excitation wavelengths of 325 nm also allow the study of Al x Ga 1 x N surface properties for aluminium compositions up to x D 0.23. 20,21 Deep-UV micro-Raman spectroscopy is necessary to probe the surface layer of Al x Ga 1 x N films of higher aluminium compositions due to their larger bandgap (using, for example, a frequency-doubled Ar laser (244 nm) as excitation source 22 up to an aluminium composition of x D 0.71). Note that the Al x Ga 1 x N bandgap increases with increasing aluminium composition x.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,11 There have been few reports about the thermal stability of AlGaN / GaN heterostructures. 12,13 It was found that the HEMT channel temperature increases rapidly with dissipated power and, at 6 W / mm, the temperature reaches ϳ320°C for sapphire substrate. 14 Investigation into the thermal stability of AlGaN / GaN heterostructures is desirable for further device applications.…”
mentioning
confidence: 98%
“…Therefore, use of faceted lateral growth has the potential to obtain crack-free thick AlGaN films. The thermal properties of AlGaN have been studied by Kuball et al 62 employing ultraviolet Raman scattering spectroscopy. The degradation pathway of Alo.72Gao.2sN was monitored for hightemperature treatments.…”
Section: Dislocation and Morphology Analysismentioning
confidence: 99%